MANAJEMEN SEKOLAH REGULER DALAM IMPLEMENTASI PENDIDIKAN INKLUSIF: SEBUAH STUDI KASUS DI SDN CINANGGERANG I - Agi Hamdani; Nenden Ineu Herawati (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This research discusses the management of regular elementary schools in implementing inclusive education at SDN Cinanggerang I. The study topics in this research are: (1) What is the description of school management in implementing inclusive education, (2) what are the challenges and obstacles encountered in implementing inclusive education . The research method applied is a descriptive qualitative method. The data sources for this research are school principals, teachers and students. The data collection techniques used were interviews, observation and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results of the research show that there are five elements of school management that are implemented in accommodating inclusive education, including (1) Student management, (2) Curriculum management, (3) Learning management, (4) ) Management of educators and education personnel, and (5) Management of facilities and infrastructure. There are obstacles in the implementation of inclusive education, including lack of understanding about inclusive education by both teachers and parents, (2) lack of adequate facilities and infrastructure, (3) lack of teacher competence in inclusive learning, (4) lack of support from the government, (5) lack of negative stigma towards inclusive education, especially for children with special needs